Pendidikan Karakter Bangsa - Ahmed Machfudh (STAI ALHIKMAH Jakarta, 2017)
Besides the efforts to enhance the knowledge of science and technology as well as work ethic and competitiveness, the efforts to establish the character and identity of nation are implemented through the development of religion in the form of providing education in order to realize an independent Indonesian society that is advanced, noble, dignified, and civilized. The development in the field of religion cannot be separated from the development of education, especially religious education and education in Islamicschool(madrasah)andotherreligiouspubliceducational institutions. The development of the nation’s character is directed to be part of efforts to achieve the vision of the national development as it is stated in the Long Term Development Plan of 2005-2025 namely to make Indonesia as a developed, independent, and fair nation as the foundation for the next stage of development toward fair and prosperous society in the NKRI (a unitary state of Indonesia) based on the Pancasila and the Constitution of the Republic of Indonesia 1945. Keywords : education, character education, religious education, and the nation’s character. Upaya pembentukan karakter dan jati diri bangsa, di samping peningkatan penguasaan dan ketrampilan di bidang ilmu pengetahuandanteknologi sertapeningkatanetoskerjadandaya saing, dilaksanakan melalui pembangunan agama dalam bentuk penyelenggaraan pendidikan guna mewujudkan masyarakat Indonesia yang mandiri, maju, berakhlak mulia, bermartabat, danberadab.Pembangunanbidangagamatidakdapatdilepaskan dari pembangunan pendidikan, khususnya pendidikan agama, pendidikan keagamaan, dan pendidikan pada madrasah serta lembagapendidikanumumlainnyayangbercirikhaskeagamaan. Pembangunan karakter bangsa diarahkan menjadi bagian yang tak terpisahkan dari upaya pencapaian visi pembangunan nasional sebagaimana tertuang dalam Rencana Pembangunan Jangka Panjang Tahun 2005-2025, yaitu mewujudkan Indonesia sebagai bangsa yang maju, mandiri, dan adil sebagai landasan bagi tahap pembangunan berikutnya menuju masyarakat adil sebagai landasan bagi tahap pembangunan berikutnya menuju masyarakat adil makmur dalam NKRI beradasarkan Pancasila dan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Kata kunci: Pendidikan, pendidikan karakter, pendidikan agama, karakter bangsa.